(untitled) (Research, Society and Development, 2021)
Imaging exams combined with clinical aspects are of paramount importance for the correct diagnosis and treatment of the problem case experienced by patients who seek health services. Among the exams we can mention the Panoramic Radiography (PR) and the Cone Beam Computed Tomography (CBCT), which have several indications in the dental field. The objective of this work was to analyze the main indications for carrying out these tests. The requests were kindly granted by the Federal University of Ceará - Campus Sobral, totaling 252 PRs and 186 CBCTs carried out from August to October 2019. The indications were organized into nine groups: ATM, Surgery, Endodontics, Stomatology, Implantology, Pediatric Dentistry, Periodontics, Other Indications and No Indications. According to the results, we noticed that the greatest number of indications for PRs was in Surgery, highlighting the evaluation of impacted third molars, while the main indication of CBCTs was for implant dentistry, highlighting the preoperative planning for implant placement. It is also worth mentioning the high prevalence of exam requests without a described indication. Therefore, it is concluded that there is a need for education at the university level to correctly fill out the application forms, in addition to establishing a clinical protocol to standardize such indications in order to improve the documentation of cases. In addition, whatever the imaging exam chosen for the problem case in question, its need must always be taken into account, in order not to expose the patient to unnecessary radiation dose.